2021
DOI: 10.37797/ig.40.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease is Associated with an Increased Mortality in Adult Patients with Group B Streptococcus Invasive Disease

Abstract: Background: Group B Streptococcus (GBS) is a significant cause of invasive disease among adult non-pregnant patients with increasing incidence and mortality rates. Although non-alcoholic fatty liver disease (NAFLD) is associated with components of metabolic syndrome previously recognized as risk factors for GBS, the impact of NAFLD on GBS course and outcomes is unknown. Methods: We conducted a retrospective cohort study of all non-pregnant adult patients diagnosed with invasive GBS infection during a 15-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Notably, patients with NAFLD more frequently developed AKI and required CRRT, reflecting a more severe disease. Similar was described in a cohort of patients with invasive group B streptococcus infections and NAFLD [ 25 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Notably, patients with NAFLD more frequently developed AKI and required CRRT, reflecting a more severe disease. Similar was described in a cohort of patients with invasive group B streptococcus infections and NAFLD [ 25 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the pre-COVID era, data associating NAFLD with adverse outcomes in serious infections were scarce, although consistent [ 20 , 21 , 22 , 23 , 24 , 25 ]. In COVID-19, numerous studies reported an association of NAFLD with increased COVID-19 severity and mortality [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with NAFLD might have a higher risk for infections due to the concomitant presence of obesity or diabetes mellitus, few studies that included NAFLD in the analysis consistently showed its outcome impact independently of the metabolic syndrome components [20]. So far, this was suggested for communityacquired pneumonia, bacteriaemia of gastrointestinal origin, sepsis and urinary tract infections [21][22][23][24][25]. Recently, we have shown that NAFLD is a risk factor for in-hospital CDI development in elderly patients treated with systemic antimicrobial therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal failure, qSOFA ≥ 2, endocarditis, and NAFLD were all independently linked to in-hospital mortality. The study concluded that NAFLD is associated with higher mortality in individuals with invasive GBS disease [67]. These studies did not stratify the severity of liver disease and its correlation with the severity of bacteremia, RBIs and their outcome.…”
Section: Nafld Bacteremia and Recurring Bacterial Infectionsmentioning
confidence: 94%